Legal Interpretation of the Position of the Papuan People's Assembly in the Expansion of Provinces within the New Autonomous Region of Papua - Decky DA Wospakrik (Dinasti Research, 2025)
The purpose of this study is to analyze changes in the legislation on Papua's special autonomy with the aim of expanding the province of Papua. The purpose of expansion is carried out by first making changes to the legislation related to Papua's special autonomy with fast track legislation). This study uses a normative method, which traces the legislation related to interpreting the changes in the regulations. The results of the study on changes to the Law by means of fast track legislation (FTL), provide an interpretation that the expansion of the province of Papua can be carried out by changing Article 76 in the Special Autonomy Law before the change by placing the word